Medical social workers' and clinical psychologists' understanding of autism spectrum disorders: A Nigerian Study - Monday Nwite Igwe; Emmanuel Omamurhomu Olose; Okwudili Obayi; Chinonyerem Igwe; Ugomma A Ude; Edmund Ndudi Ossai (Journal of Biology and Medicine - Peertechz Publications, 2022)
Introduction: Autism is a neurodevelopmental disorder characterised by difficulties in social communication and interaction, repetitive patterns of behaviour and focused interests and activities. Medical social workers and Clinical psychologists play vital roles in identifying and supporting autistic children with their families. They may help with therapy, rehabilitation, crisis interventions and outreach services. Adequate knowledge about Autism Spectrum Disorders (ASD) among Medical social workers and Clinical psychologists may enhance early recognition, diagnosis, appropriate referral and interventions that are known to improve prognosis in autistic children. This study determined Medical social workers' and Clinical psychologists' understanding of ASD. Materials and methods: Socio-demographic and Knowledge About Childhood Autism among Health Workers (KCAHW) questionnaires were administered to consenting 63 Medical social workers and 35 Clinical psychologists.  Results: Sixty-three Medical Social workers and 35 Clinical psychologists participated in the study. The mean age of Medical social workers was 42.1 ± 8.6 years and 41.0 ± 8.9 years for Clinical psychologists (P = 0.525). Clinical psychologists who were males were 42.9% and 41.3% were male Medical social workers (P = 0.879). Medical social workers who have ever managed a child with autism in the course of their career were 42.9% while Clinical psychologists were 40.0% (P = 0.784). The mean knowledge score for variables in domain 1 for Clinical psychologists was 6.34 ± 1.78 while Medical social workers scored 5.40 ± 2.30 (P = 0.038). The score in domain 2 for Clinical psychologists was 0.91 ± 0.28 while Medical social workers scored 0.71 ± 0.46 (P = 0.009). The mean total score for Clinical psychologists was13.00 ± 2.86 whereas Medical social workers scored 11.51 ± 3.43 (P = 0.031). Conclusion: Clinical psychologists significantly scored higher than Medical social workers in knowledge mean scores in domains 1 and 2 and total mean scores. The scores of Clinical Psychologists though higher than scores by Medical social workers are still considered inadequate. It is recommended that the training curriculum of Medical social workers and Clinical psychologists should involve more tutorials, teachings and clinical rotations that would expose them to different aspects of ASD.